Efficient Fault Detection Algorithm in Fiber Optic Communication Systems - Simatupang, Joni Welman; Pukhrambam, Puspa Devi (JURNAL TEKNIK INFORMATIKA, 2022)
Primary concern of optical communication system is the signal loss, which need to be traced precisely to enhance the efficiency of the system. Among numerous available techniques, optical time domain reflectometer (OTDR) is the most suitable one for characterizing and tracing the losses. It measures the fraction of a probe pulse that scatters back from the fiber optic cable. Due to the presence of small levels of backscattering in single-mode fiber at long wavelengths, very sensitive optical detector is necessary to achieve sufficient range performance. In the present research, a novel yet simple approach has been demonstrated to understand the range of optical fiber cable feasibility on fault detection and rectification technique. The actual place of fault is marked with the variation in the measured values of OTDR. Thus, it becomes a difficult task to trace and locate the actual place of fault detection, which leads to an inefficient rectification method. The observed values of OTDR shows a gradual decrease of accuracy in locating the actual place of fault. To resolve these issues, here we try to develop an algorithm which is able to easily and efficiently trace the exact location of fault on earth.